Pelatihan Bantuan Hidup Dasar Untuk Masyarakat Umum - Antin Trilaksmi; Diani Nazma; Lira Panduwaty; Christian; Karlina Mahardieni (CV. Multi Kreasi Media, 2025)
Basic life support is the initial activity to restore respiratory and/or circulatory function to someone who has experienced respiratory arrest and/or cardiac arrest. The main goal of basic life support is to restore the body's vital functions, namely breathing and circulation, to prevent death. Basic life support can actually be carried out by ordinary people before paramedics or a medical team arrives at the accident scene. However, it is a shame that knowledge regarding basic life support is still low among ordinary people. Lack of knowledge of Basic Life Support among lay people is one of the factors causing the high death rate due to sudden cardiac arrest, therefore increasing public knowledge about basic life support is very necessary. This community service activity (PKM) teaches and trains the general public so they can provide first aid to cardiac arrest patients. With this increase in knowledge, it is hoped that the public will be able to provide first aid for cardiac arrest before medical personnel arrive, thereby increasing the life expectancy of patients with sudden cardiac arrest outside the hospital. The activity was carried out at the Trisakti Nagrak campus, Ciangsana village, Gunung Putri sub-district, Bogor, on November 9 2024. The training was carried out using a lecture method, demonstration of basic life support actions, then participants practiced the material taught on a mannequin and ended with a question and answer session. Participants were given pretest and posttest questions before and after the training session to assess how far the participants' BHD knowledge had improved. The output of this pkm activity is publication in accredited national journals, creation of Intellectual Property Rights (HKI) and publication in public media (You Tube).